ENTREPRENEURIAL SELF-EFFICACY DRIVES AND AMPLIFIES PERCEIVED OPPORTUNITY TOWARDS THE ENTREPRENEURIAL INTENTION OF ULOS WEAVERS GENERATION - Sitinjak, Imelda; Malau, Anne Rumondang (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
The basic problem of family business succession planning is whether the generation intends to continue the family business, so this study aims to examine the intention of generations to continue their family's ulos weaving business based on the planned behavior theory (Ajzen, 1991). The Purposive Random Sampling method was selected and obtained as many as 131 generations of ulos weavers aged at least 15 years in North Tapanuli Regency who were collected using the snowball technique. Data analysis used the Structural Equation Model with the Lisrel program. The findings of this study indicate that entrepreneurial self-efficacy (ESE) plays a role in encouraging perceived opportunity (PO) towards entrepreneurial intention (EI). However, the role of entrepreneurial self-efficacy (interaction with PO to become ESEXPO) cannot strengthen PO towards EI. Gender effect testing found that women's EI was higher than men's because it was related to weaving skills. The weakness of this study is the cross-sectional time dimension so the implications for future research are the longitudinal time dimension, especially for testing moderation as well as in different contexts for testing the role of moderation or results that are inconsistent with a combination of theories so as to find novelty. In addition, other predictors and controls need to be added to enrich research in the field of family entrepreneurship. The implication for family business actors is to have a succession plan long before being 'forced' or as early as possible so that entrepreneurial self-efficacy and perceived opportunity arise, as well as other factors (internal and external) that are needed by the next generation of family businesses.